The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1016/s0896-6273(00)80251-2
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Brain rsec6/8 Complex

Abstract: rsec6 and rsec8 are two components of a 17S complex in mammalian brain that is homologous to the yeast 834 kDa Sec6/8/15 complex which is essential for exocytosis. Purification and partial amino acid sequencing of the mammalian rsec6/8 complex reveals that it is composed of eight novel proteins with a combined molecular weight of 743 kDa. The complex is broadly expressed in brain and displays a plasma membrane localization in nerve terminals. Membrane associated rsec6/8 complex coimmunoprecipitates with syntax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
230
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(244 citation statements)
references
References 36 publications
11
230
0
1
Order By: Relevance
“…Hybridoma production, ELISA and Western blot screening, subcloning, and expansion were carried out as described previously (Hsu et al, 1996). Goat polyclonal antibodies against syntaxin 17 were prepared by immunization with bacterially expressed rat syntaxin 17 produced as described above.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridoma production, ELISA and Western blot screening, subcloning, and expansion were carried out as described previously (Hsu et al, 1996). Goat polyclonal antibodies against syntaxin 17 were prepared by immunization with bacterially expressed rat syntaxin 17 produced as described above.…”
Section: Antibodiesmentioning
confidence: 99%
“…Individual protein bands were cut out and subjected to in-gel proteolysis by trypsin. Aliquots of the digested peptides were subjected to mass spectrometry, and remaining peptide mixtures were fractionated by HPLC and microsequenced as described previously (Hsu et al, 1996). In addition, the identities of the precipitated proteins were verified by Western blot analyses.…”
Section: Immunoprecipitation Experiments and Protein Sequencingmentioning
confidence: 99%
“…Although there is no known mammalian homolog for Bud4p, a counterpart exists for each septin and exocyst subunit. The mammalian exocyst [Sec6-Sec8 (EXOC3-EXOC4) complex] has been co-purified and immunoprecipitated with septins (Hsu et al, 1996;Hsu et al, 1998;Hsu et al, 1999); like its yeast counterpart, it was found to influence polarized vesicle delivery (Hsu et al, 1999). Mammalian septins were individually identified and implicated in cytokinesis, exocytosis, vesicle-targeting and membrane dynamics (Spiliotis and Nelson, 2006;Beites et al, 1999;Trimble, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several large protein complexes have been proposed to help target vesicles to a particular membrane domain. The exocyst (sec6/8 complex), composed of eight proteins, is thought to help recruit Golgiderived vesicles to the plasma membrane at the final step of the secretory pathway (Hsu et al, 1996;TerBush et al, 1996;Kee et al, 1997). The multisubunit TRAPP I and Vps52/ 53/54 complexes are believed to serve analogous functions during ER-to-Golgi and endosome-to-Golgi trafficking, respectively (Conibear and Stevens, 2000;Sacher et al, 2001).…”
Section: Introductionmentioning
confidence: 99%